Rapid Detection and Molecular Typing of Dengue Virus by Using Multiplex-Nested-RT-PCR - Nastiti Wijayanti; Hera Nirwati; Tri Wibawa; Aris Haryanto; S. Sutaryo (Universitas Gadjah Mada, 2006)
world. We have evaluated the combination of one-step RT-PCR and multiplex nested PCR assays for detectingdengue viruses from clinical samples. Twelve patients were screened for the dengue virus, using a pair of primersthat conserve for several Flavivirus. The results showed that in 12 suspect patients, 100% were positive for Flavivirusand there are some genotypic variation among them, that indicated by several RT-PCR products higher than 511 bp,the expected product for RT-PCR. Further assay was performed to clarify the presence and serotypes of dengue virususing multiplex nested PCR. Serotyping results indicated that 83,3% of samples can be confirmed for dengue virus.Among the dengue virus positive 16,7 % are dengue-2, 16.7 % are dengue-3, and the most common 50% are dengue-4,whereas dengue-1 were not found among the patients. The combination of RT-PCR and multiplex nested PCR assaycan be used for rapid analysis dengue samples in early phase which is potentially useful for clinical, epidemiologyand also evolutionary studies.Key words: Flavivirus, dengue virus, serotype, RT-PCR, multiplex nested PCR